KITAAB DURUSU AL-LUGHAH AL-‘ARABIYYAH WA ATSARUHU FII TADRIIS AL-LUGHAH AL-‘ARABIYYAH ‘ALAA MUNJIZ THAALIBAAT AS-SHAF AS-SABI’ “E” FII MADRASAH TSANAWIYYAH LILBANAAT BI MA’HAD UMMUL QURO AL-ISLAMI BOGOR - Aryanti; Muh Abrar; Lukman Taufik Akasahtia (SHAWTUL ARAB, 2022)
This study is set in the background by the language textbook, which has a broad and easy discussion that can attract students to study. The purpose of this study is to find out the effect of language textbooks on students' achievement. The research method used is descriptive, using a quantitative approach. This research place is in the secondary school of the Umm Al-Qura Islamic Institute, Bogor, in the seventh semester, for girls. The sampling technique is the saturated sample. Based on the results of the correlation test between the two variables. The book of language lessons and student achievement has a positive relationship with a sufficient Pearson correlation value of 0.451. It can be concluded from these results, that the more the use of a language textbook increases, the student's achievement increases, and on the contrary, the decrease in the use of a language textbook, the student's achievement decreases